TNF-α, CXCL8, big ET-1 and hsCRP in patients with chronic obstructive pulmonary disease - Marević, Sanja (Array, 2008)
Summary: COPD (chronic obstructive pulmonary disease) is a chronic progressive inflammatory disease characterised by limitations in lung airflow that is not fully reversible. The concentrations and correlations of TNF-α, CXCL8, big ET-1 and hsCRP were investigated in healthy non-smokers, healthy smokers and patients with COPD in order to study their possible role in the pathophysiology of COPD. The concentrations of TNF-α, CXCL8 and big ET-1 were not statistically different between the experimental groups. No significant differences for the measured analytes were found between smokers and the non-smokers in the control group. The Spearman coefficient of correlation between the concentrations of TNF-α and CXCL8 was r = 0.638 (p<0.0001). However, the concentration of hsCRP was significantly higher in patients with COPD than in the control group (p = 0.0004). hsCRP proved to be a more sensitive diagnostic parameter than TNF-α, CXCL8 and big ET-1 in the systemic circulation in patients with COPD